Appeal By Objection From The Personal Claimant In The Criminal Court - حماد, مسعود (Latakia University Journal - Economic and Legal Sciences Series, 2023)
This research dealt with the subject of the right of the personal prosecutor to object to the penal judgment in absentia according to the Syrian law. The research required talking about the effect of the absence of the personal plaintiff from the civil lawsuit established according to the general claim in the first demand. And talk about the extent of eligibility of the personal prosecutor to object to the second demand. Where we discussed the first requirement to talk about the law of assets applicable to the civil lawsuit before the criminal court, and the impact on the absence of personal plaintiff from the presence, both before or after the fall of the public right, and in the second demand we talked about the position of the judicial direction of granting personal plaintiff The right to object to the criminal judgment in absentia, and judicial developments in this regard, in addition to knowledge of the jurisprudential opinion of granting this right, and the arguments that they have taken in order to do so. The research reached a number of results, the most important: There is a legislative lack in determining the meaning of the (sentenced) in Article 205 of the Code of Criminal Procedure of Syria. Keywords: Appeal by objection‚ default judgment‚ Absence of the personal claimant.